Controlled Design of a Robust Hierarchically Porous and Hollow Carbon Fiber Textile for High‐Performance Freestanding Electrodes - Quanxiang Li; Jiemin Wang; Chao Liu; Seyed Mousa Fakhrhoseini; Dan Liu; Liangzhu Zhang; Weiwei Lei; Minoo Naebe (Advanced Science, 2019)
Abstract For most carbon‐based materials, hierarchical porous structure including well‐defined macropores, mesopores, and micropores is commonly seen in 3D aerogels, monoliths, or some carbothermic natural biomass. However, because of the filiform character and long draw ratio, it is difficult to achieve such pore network as well as attain excellent mechanical performance in a 1D single carbon fiber system. To address this issue, an innovative hierarchical porous and hollow carbon textile (HPHCT) is developed via the “dynamic template (KOH, SiO2, and Al2O3) calcination” strategy. Unlike conventional one‐step activated carbonized fiber simply with meso or micropores, the fabricated textile generates honeycomb‐like macropores uniformly spreading on fiber surface. More importantly, the ultra‐lightweight yet flexible HPHCT is mechanically robust, superior to ordinary carbonized one. In addition, it delivers high capacitance of maximum 220 F g−1 as well as keeping long term stability with 100% retention after 10 000 cycles as freestanding electrodes in supercapacitor. Meanwhile, the all‐solid integrated symmetric HPHCT supercapacitors demonstrates its high potential in powering electronics for wearable energy storage application.